Effect of 660 nm Light-Emitting Diode on the Wound Healing in Fibroblast-Like Cell Lines - Myung-Sun Kim; Yong-Ick Cho; Min-Suk Kook; Sang-Chul Jung; Young-Hyun Hwang; Byung-Hoon Kim (International Journal of Photoenergy)
Light in the red to near-infrared (NIR) range (630–1000 nm), which is generated using low energy laser or light-emitting diode (LED) arrays, was reported to have a range of beneficial biological effects in many injury models. NIR via a LED is a well-accepted therapeutic tool for the treatment of infected, ischemic, and hypoxic wounds as well as other soft tissue injuries in humans and animals. This study examined the effects of exposure to 660 nm red LED light at intensities of 2.5, 5.5, and 8.5 mW/cm2 for 5, 10, and 20 min on wound healing and proliferation in fibroblast-like cells, such as L929 mouse fibroblasts and human gingival fibroblasts (HGF-1). A photo illumination-cell culture system was designed to evaluate the cell proliferation and wound healing of fibroblast-like cells exposed to 600 nm LED light. The cell proliferation was evaluated by MTT assay, and a scratched wound assay was performed to assess the rate of migrating cells and the healing effect. Exposure to the 660 nm red LED resulted in an increase in cell proliferation and migration compared to the control, indicating its potential use as a phototherapeutic agent.